Does acupuncture therapy affect peripheral inflammatory cytokines of major depressive disorder? A protocol for the systematic review and meta-analysis - Zhao, Ya-Nan; Zhang, Shuai; Chen, Yu; Wang, Yu; Chen, Hao; Duan, Yu-Ting; Li, Shao-Yuan; Zhang, Zi-Xuan; Wang, Yi-Fei; Xin, Chen; Li, Liang; Rong, Pei-Jing (Frontiers in Neurology, 2022)
Background: Acupuncture is widely used as adjuvant therapy for major depressive disorder (MDD). There is robust evidence that inflammation is closely associated with MDD. Up to date, only a few numbers of studies have investigated the potential relationship between acupuncture and the change of inflammatory biomarkers in patients of MDD. And the results are inconsistent among studies. The current study aims to provide a comprehensive, systematic review of the association between acupuncture and changes of peripheral inflammation of patients with MDD, and clarify the alterations of inflammatory cytokines before and after acupuncture treatment by meta-analysis.Methods and analysis: This study will be conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta- Analyses guidelines. Eligible randomized controlled trials (RCTs) reporting acupuncture, with inflammatory cytokines as the outcome measured before and after intervention in patients with MDD, were searched in electronic databases, such as Pubmed, Embase, Cochrane, SinoMed, Wanfang, China national knowledge infrastructure (CNKI) and Chongqing VIP(CQVIP). Primary outcomes of interest will be validated measures for levels of inflammatory cytokines before and after acupuncture treatment in patients with MDD.Discussion: Acupuncture can drive anti-inflammatory effects, as well symptom changes in MDD, which may represent a viable, multi-faceted treatment approach in MDD.